Efficacy of different dry-cow intramammary antimicrobial products on the prevalence of mastitis in a high-producing dairy herd - Lourens, D.C. (Dirk Cornelius) (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2004.